Procedure for determining the appropriate payer of social security contributions - Ceglarska-Jóźwiak, Joanna (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The study discusses the most important issues regarding the determination of the appropriate payer of social insurance contributions. The payer, as a co-contractor of social insurance, performs a number of important tasks related to both the collection of contributions and the implementation of the right to insurance benefits. For this reason, it is important that the entity acting as the payer is correctly identified. In case of doubts, the Social Insurance Institution carries out proceedings to determine the appropriate payer taking into account the factual findings.